2016
DOI: 10.3390/ijerph13100999
|View full text |Cite
|
Sign up to set email alerts
|

Sun Exposure and Its Effects on Human Health: Mechanisms through Which Sun Exposure Could Reduce the Risk of Developing Obesity and Cardiometabolic Dysfunction

Abstract: Obesity is a significant burden on global healthcare due to its high prevalence and associations with chronic health conditions. In our animal studies, ongoing exposure to low dose ultraviolet radiation (UVR, found in sunlight) reduced weight gain and the development of signs of cardiometabolic dysfunction in mice fed a high fat diet. These observations suggest that regular exposure to safe levels of sunlight could be an effective means of reducing the burden of obesity. However, there is limited knowledge aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 133 publications
(179 reference statements)
1
29
0
1
Order By: Relevance
“…7 Other reports suggest that nbUVB therapy modifies the skin microbiome with these changes linked to the capacity of this therapy to control psoriatic flare. 8 In addition, pre-clinical [9][10][11] and human studies [12][13][14] indicate that UVR may be beneficial for metabolic health. Adult mice fed a high fat diet and exposed repeatedly to sub-erythemal (non-burning) UVB (1 kJ/m 2 ) over 12 weeks gained less weight, exhibited reduced metabolic dysfunction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…7 Other reports suggest that nbUVB therapy modifies the skin microbiome with these changes linked to the capacity of this therapy to control psoriatic flare. 8 In addition, pre-clinical [9][10][11] and human studies [12][13][14] indicate that UVR may be beneficial for metabolic health. Adult mice fed a high fat diet and exposed repeatedly to sub-erythemal (non-burning) UVB (1 kJ/m 2 ) over 12 weeks gained less weight, exhibited reduced metabolic dysfunction (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…small sample size), the initial vitamin D status of participants (e.g. not being vitamin D-deficient at the start of the trial) and the amount and timing of vitamin D supplementation; however, the biological activity of non-vitamin D sun-induced mediators like nitric oxide (Feelisch et al 2014, Liu et al 2014, Fleury et al 2016 may also explain the lack of effects observed.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic data presented in this interesting review suggests that long-term exposure to safe levels of ultra-violet radiation (UVR) has protective effects against the development of obesity and cardiovascular dysfunction beyond those induced by the cutaneous synthesis of vitamin D3 through factors such as the induction of cutaneous NO secretion [1]. Evidence from studies achieving comparable vitamin D status (serum 25-hydroxyvitamin D (25OHD) concentrations) is quoted [2], where features of metabolic syndrome were better suppressed by the UVR doses used than by supplementation.…”
mentioning
confidence: 99%